برنامج قائم على نظرية المرونة المعرفية لتنمية الوعي بالتدريس المتمايز لدى الطالبات معلمات اللغة العربية منخفضات معتقدات الفاعلية الذاتية للتدريس - عبدالعظيم، ريم أحمد (جامعة عين شمس - كلية التربية - الجمعية التربوية لتدريس اللغات, 2018)
This research aims at developing a program based on the cognitive flexibility theory, and measuring its effectiveness in developing low self-efficacy Arabic student teachers’ awareness of distinguished teaching. The problem of the study lies in the lack of awareness of distinguished teaching on the part of female Arabic student teachers, and their inability to deal with the students with different characteristics and needs. Meanwhile, there are currently no suitable training programs based on modem educational theories- such as the cognitive flexibility theory- that could help those student teachers be aware of distinguished teaching and how to implement it in the educational process. Besides, those student teachers have low self-efficacy teaching beliefs and this can influence their Arabic instructional practices negatively. To solve this problem, the present research followed a set of procedures, including: preparing an inventory of the distinguished teaching and classroom management skills Arabic female student teachers have to master; and identifying the guidelines of building the cognitive flexibility theory-based program, and its and components (i.e., objectives, content, teaching strategies, activities and aids, and evaluation methods). To measure the effectiveness of the program, the following measurement instruments were used: a scale of teaching self- efficacy, a cognitive test of distinguished teaching, an observation card of the distinguished teaching and classroom management skills, and a scale of attitudes towards distinguished teaching. The sample of the research was selected from female Arabic student teachers studying at the Girls’ College, Ain-Shams University. The proposed program was taught to the students and the research instruments were administered to them before and after the program. The research found that the program was effective in developing the students’ awareness of distinguished teaching and developing their high teaching self-efficacy beliefs.
هدف هذا البحث إلى بناء برنامج قائم على نظرية المرونة المعرفية، وقياس فاعليته في تنمية الوعي بالتدريس المتمايز لدى الطالبات معلمات اللغة العربية منخفضات معتقدات الفاعلية الذاتية للتدريس. وتحددت مشكلة البحث في غياب وعي الطالبات معلمات اللغة العربية بالتدريس المتمايز، وعدم قدرتهن على التعامل مع التلاميذ مختلفي الخصائص والاحتياجات، في الوقت الذي لا تتوافر فيه البرامج التدريبية المناسبة والقائمة على النظريات التربوية الحديثة – مثل نظرية المرونة المعرفية – لتعريفهن بالتدريس المتمايز وكيفية توظيفه في العملية التعليمية، هذا فضلا عن انخفاض معتقدات الفاعلية الذاتية للتدريس لدى هؤلاء الطالبات، وانعكاساتها السلبية على ممارساتهن وأداءاتهن التدريسية للغة العربية. وللوصول إلى حل هذه المشكلة سار البحث في مجموعة من الخطوات لعل من أهمها: إعداد قائمة بمهارات التدريس والإدارة للصف المتمايز التي ينبغي تنميتها لدى الطالبات معلمات اللغة العربية، وتحديد أسس بناء البرنامج القائم على نظرية المرونة المعرفية، وتحديد مكوناته المتمثلة في: أهدافه، ومحتواه، واستراتيجيات التدريس والأنشطة المستخدمة فيه، والوسائط التعليمية المعينة على تحقيق أهدافه، وأساليب تقويمه. ولقياس فاعلية البرنامج وقدرته على تحقيق أهدافه تم إعداد أدوات القياس والتي تمثلت في مقياس معتقدات الفاعلية الذاتية للتدريس، واختبار لقياس الجانب المعرفي للتدريس المتمايز، وبطاقة ملاحظة لمهارات التدريس والإدارة للصف المتمايز، ومقياس الاتجاه نحو التدريس المتمايز، وقد تم اختيار مجموعة البحث من الطالبات معلمات اللغة العربية بكلية البنات بجامعة عين شمس، وتم تطبيق أدوات القياس عليها قبليا، ثم تدريس البرنامج المقترح للطالبات المعلمات، ثم تطبيق أدوات القياس عليها بعديا. وتوصل البحث إلى مجموعة من النتائج لعل من أهمها: فاعلية البرنامج القائم على نظرية المرونة المعرفية في تنمية الوعي بالتدريس المتمايز ورفع معتقدات الفاعلية الذاتية للتدريس لدى مجموعة البحث من الطالبات معلمات اللغة العربية.
Keywords: البرامج التدريسية -- التنمية المهنية -- المرونة المعرفية -- التدريس المتمايز -- طلاب الجامعات -- الطلاب المعلمين -- تدريس اللغة العربية